Fabrication of nanofiber mats from electrospinning of functionalized polymers - (:unkn) unknown (IOP PUBLISHING LTD, 2014)
Electrospinning technique enabled us to prepare nanofibers from synthetic and natural polymers. In this study, it was aimed to fabricate electrospun poly(vinyl alcohol) (PVA) based nanofibers by reactive electrospinning process. To improve endurance of fiber toward to many solvents, PVA was functionalized with photo-crosslinkable groups before spinning. Afterward PVA was crosslinked by UV radiation during electrospinning process. The nanofiber mats were characterized by scanning electron microscopy (SEM). The results showed that homogenous, uniform and crosslinked PVA nanofibers in diameters of about 200 nm were obtained. Thermal stability of the nanofiber mat was investigated with thermal gravimetric analysis (TGA). Also the potential use of this nanofiber mats for tissue engineering was examined. Osteosarcoma (Saos) cells were cultured on the nanofiber mats.